Duality for Multiobjective Fractional Variational Problems - Mishra, S.K.; Mukherjee, R.N. (My University, 1994)
A class of multiobjective fractional variational problems is considered and duals are formulated. Under concavity assumptions on the functions involved, duality theorems are proved through a parametric approach to relate efficient solutions of the primal and dual problems. We generalize those results for control problems also.
Keywords: Fractional Variational; Multiobjective; Duality